2013
DOI: 10.1111/1462-2920.12153
|View full text |Cite
|
Sign up to set email alerts
|

An improved cell separation technique for marine subsurface sediments: applications for high‐throughput analysis using flow cytometry and cell sorting

Abstract: SummaryDevelopment of an improved technique for separating microbial cells from marine sediments and standardization of a high-throughput and discriminative cell enumeration method were conducted. We separated microbial cells from various types of marine sediment and then recovered the cells using multilayer density gradients of sodium polytungstate and/or Nycodenz, resulting in a notably higher percent recovery of cells than previous methods. The efficiency of cell extraction generally depends on the sediment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
125
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(130 citation statements)
references
References 25 publications
5
125
0
Order By: Relevance
“…Within the lithological setting of the Shimokita coalbed biosphere, where environmental conditions changed drastically after shallow coastal sediments subsided below sealevel since the Miocene, we have detected the most deeply buried microbial communities studied to date . Microbial cells were detached from sediments by a multi-layer density gradient technique (Morono et al, 2013), and then their concentration was determined by both manual and computer-based microscopic image analyses (Morono et al, , 2013Morono and Inagaki, 2010). The cell count analysis revealed that cell concentrations in deep sediments below ∼ 1.5 km b.s.f.…”
Section: Microbiology and Biogeochemistrymentioning
confidence: 99%
“…Within the lithological setting of the Shimokita coalbed biosphere, where environmental conditions changed drastically after shallow coastal sediments subsided below sealevel since the Miocene, we have detected the most deeply buried microbial communities studied to date . Microbial cells were detached from sediments by a multi-layer density gradient technique (Morono et al, 2013), and then their concentration was determined by both manual and computer-based microscopic image analyses (Morono et al, , 2013Morono and Inagaki, 2010). The cell count analysis revealed that cell concentrations in deep sediments below ∼ 1.5 km b.s.f.…”
Section: Microbiology and Biogeochemistrymentioning
confidence: 99%
“…A standardized, high-throughput cell counting method, presented by Yuki Morono (Fig. 1), will be included in the handbook as one of the recommendations for on-site analysis (Morono et al, 2013). Additional methods will be considered with the understanding that the handbook should be updated as technologies advance.…”
Section: Deep Bio Handbookmentioning
confidence: 99%
“…This method can be used repeatedly at multiple drill sites to reduce human errors and provide better connectivity between projects. (Figure is being used with permission from Yuki Morono; Morono et al, 2013. ) chemical characteristics (Mills et al, 2012b).…”
Section: Deep Bio Handbookmentioning
confidence: 99%
“…Since Leg 190, drastic advances in cell separation and enumeration technologies for sediment core samples have lowered the MQL by a factor of ~10,000 (e.g., Kallmeyer, 2011;Morono et al, 2009Morono et al, , 2013Morono et al, , 2014Morono and Inagaki, 2010). Likewise, the new capacities offered in the "omics" era for elucidation of taxonomic composition (e.g., Inagaki et al, 2006;Sogin et al, 2006), metabolic activity, and function at single-cell to community levels (e.g., Biddle et al, 2008;Lloyd et al, 2013;Orsi et al, 2013), as well as new molecularisotopic techniques that link biomass to substrate pools (e.g., Biddle et al, 2006;Morono et al, 2011;Wegener et al, 2012) and central metabolic intermediates to distinct geomicrobiological processes (e.g., Heuer et al, 2006Heuer et al, , 2009Zhuang et al, 2014;Wang et al, 2015), allow entirely new approaches to study microbial life close to the limit of the deep biosphere.…”
Section: Introductionmentioning
confidence: 99%